YouTube and kids: maternal influence on children’s learning experiences / Nur Afiqah Ab. Latif, Che Nooryohana Zulkifli and Anis Shaari - Ab. Latif, Nur Afiqah; Zulkifli, Che Nooryohana; Shaari, Anis (Universiti Teknologi MARA, Perlis, 2024)
Children in this digital era can learn from numerous content available on YouTube. This study delves into the influence of maternal guidance on children’s learning experiences through YouTube. By referencing Feuerstein’s Mediated Learning Experience (MLE) theory, the study seeks to uncover the various approaches mothers employ to navigate YouTube’s content, enhancing children’s learning experiences. Through qualitative research methods, specifically interviews, this investigation also aims to determine the types of knowledge children aged three to nine acquire from YouTube videos. The findings illustrate the mothers’ active participation in children’s learning - asking questions, discussing the content, singing along, providing explanations, and connecting to real life - has prepared the children to improve their cognitive, affective, and psychomotor development. The results provide important insights into the essential role of maternal involvement in shaping children’s knowledge acquisition on YouTube, with valuable implications for parents, educators, and instructional content developers.